2020
DOI: 10.1021/acs.iecr.0c02284
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Interfacial Adhesion between Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) and Silica Particles

Abstract: To improve the mechanical properties of biodegradable bioplastic poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), a filler made up of silica particles (SiO 2 ) is mixed with PHBH; however, SiO 2 shows low compatibility with PHBH. Herein, to enhance the interfacial adhesion of SiO 2 and PHBH, the PHBH-grafted SiO 2 (SiO 2 −PHBH) fillers were prepared from propargyl-terminated PHBH and azide-modified SiO 2 by click chemistry. Scanning electron microscopy revealed that SiO 2 −PHBH fillers dispersed uniformly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The tensile strength, storage modulus at room temperature improved by 60% and 140%, respectively, and it is suggested to have the potential for food packaging applications [243]. Other biobased inorganic fillers like silicon dioxide (SiO 2 ) [244], titanium dioxide (TiO 2 ) [245], calcium carbonate (CaCO 3 ) [246], polyhedral oligomeric silsesquioxane (POSS) [247] etc. have great potential for improvement in multiple properties of PHA based composites.…”
Section: Physical Modification Of Phamentioning
confidence: 99%
“…The tensile strength, storage modulus at room temperature improved by 60% and 140%, respectively, and it is suggested to have the potential for food packaging applications [243]. Other biobased inorganic fillers like silicon dioxide (SiO 2 ) [244], titanium dioxide (TiO 2 ) [245], calcium carbonate (CaCO 3 ) [246], polyhedral oligomeric silsesquioxane (POSS) [247] etc. have great potential for improvement in multiple properties of PHA based composites.…”
Section: Physical Modification Of Phamentioning
confidence: 99%
“…Few studies have also explored the thermal, crystallization, mechanical, and morphological properties of PHBH nanosilica nanocomposites [149][150][151][152]. It has been reported that the degradation onset temperature of pure PHBH was increased with the addition of nanosilica.…”
Section: Phbh-nanosilica (Sio2)mentioning
confidence: 99%
“…PHBH was utilized as the nanofiber matrix in the present study owing to its high biodegradability and biocompatibility. , The PHBH-aligned nanofibers with different densities were designed by mimicking the anisotropic topography of white matter, and they facilitated directional migration. The aligned nanofibers with different fiber densities were obtained via electrospinning onto the rotating collector for different spinning times (EST 20, EST 40, and EST 60).…”
Section: Resultsmentioning
confidence: 99%